COVID-19, cognitive dissonance and conspiracy theories - Vuksanovic, Mirjana (Sociološki pregled, 2020)
The aim of this paper is to point to the cognitive dissonance caused in people by different information about the new COVID-19 disease. The information originates from different professional and laymen sources and is often inconsistent. The fact that science itself has not entirely clarified the origin of the virus causing COVID-19, the symptoms, treatment protocols and consequences of disease, complicates the situation. Cognitive dissonance causes frustration, fear and stress, which, if prolonged, lead to health disorders. In search of a way out of cognitive ambiguity, many accept conspiracy theories as a solution to their own tensions.
Keywords: COVID-19; virus; health; cognitive dissonance; conspiracy theories